The Function of Educational Psychology in the Book Al-Taállamu Nadhariat Wat Thabiqat and Its Relevance to the Role of Teachers in the Learning Evaluation Process: An Integrative Study from the As-Syarqawi Perspective - Ashar Fathur Rohman; Achmad Muhlis (Penerbit Hellow Pustaka, 2025)
This study examines the function of educational psychology and its relevance to the teacher’s role in learning evaluation from As-Syarqawi’s perspective in Al-Ta’allamu Nadhariyat wa al-Tathbiqat. The study arises from the tendency of evaluation practices to focus mainly on cognitive outcomes while neglecting motivation, readiness, affective and psychomotor aspects, as well as individual differences. Employing a library research method, it analyzes classical works and modern educational psychology literature to construct an integrative perspective. The findings reveal that educational psychology helps teachers understand learners holistically, design objective and adaptive evaluations, and address learning difficulties. As-Syarqawi emphasizes that educational theory and practice must be integrated, and that evaluation should not be limited to cognitive achievement but must also consider moral, ethical, and spiritual dimensions. This integration results in a more scientific, humanistic, and comprehensive evaluation model, ultimately aiming to shape students into insan kamil.